The Nyeboe Land fault zone: a major dislocation on the Greenland coast along northern Nares Strait - Dawes, Peter R. (Meddelelser om Grønland. Geoscience, 1982)
The name Nyeboe Land fault zone is proposed for a major dislocation zone in the western part of the North Greenland fold belt, traceable along the outer coast for 300 km. Two other names are introduced: 1) the Hand Bugt fault, a reverse fault that juxtaposes strata at least as old as Cambrian to the north, against Silurian rocks to the south, and 2) the Wulff Land anticline, a major fold structure that parallels the fault zone and the outer coast. The Wulff Land anticline is regarded as having formed during the main diastrophism of the Franklinian geosyncline in Devonian time; the Nyeboe Land fault zone is considered an expression of later Tertiary reactivation. Stratigraphic data are presented that define more accurately than hitherto the Franklinian Cambro-Ordovician platform margin. This roughly coincides with the Nyeboe Land fault zone that probably had a history dating back at least to the early Palaeozoic. The location of a steep Bouguer gravity gradient in the coastal area of Nyeboe Land suggests that a deep-seated crustal structure controlled the margin of the Franklinian trough and the site of the Nyeboe Land fault zone. The Nyeboe Land fault zone, the Wulff Land anticline and the platform margin can be correlated across Nares Strait with on-line features on Judge Daly Promontory within the central Ellesmere fold belt. This indicates that any strike-slip movement along Nares Strait has only resulted in minor net displacement between Greenland and Ellesmere Island. The Nyeboe Land fault zone is correlated with the Judge Daly fault zone of Ellesmere Island to define an extensive fracture line that is oblique to Nares Strait. It is concluded that main crustal displacements in the late Phanerozoic probably took place along fracture systems oblique to Nares Strait rather than affecting the separation of Greenland and Ellesmere Island as separate plates.